Psychological intervention for a person living with amblyopia: a case study from home-based integrated care - Basharat Hussain; Muhammad Tahir Khalily; Brian Hallahan (Journal of the Pakistan Medical Association, 2023)
Amblyopia is a common developmental disability resulting in reduced visual acuity and gaze stability; it occurs in approximately 5% of the general population. Here, we present the case of an 18-year-old girl diagnosed with amblyopia. Subsequent to her diagnosis of amblyopia, she developed a depressive episode with co-morbid anxiety symptoms. She was treated with low intensity psychological intervention, Problem Management Plus, as home-based intervention. This intervention was associated both subjectively and objectively utilising psychometric measures (i.e. psychiatric interview, depression, anxiety and stress scale, general health questionnaire) with a significant amelioration of her mental state. This case provides preliminary evidence for the effectiveness of Problem Management Plus intervention and suggests that this intervention should be considered for other individuals with similar clinical presentations. Keywords: Disability, amblyopia, low vision, Patient Management Plus.